Multiple basal elements of a human hsp70 promoter function differently in human and rodent cell lines. - Greene, J; Larin, Z; Taylor, I; Prentice, H; Gwinn, K; Kingston, R (1987)
The human heat shock protein 70 (hsp70) gene is expressed constitutively in a wide variety of cells. Two separate promoter domains determine this basal level of hsp70 expression. The proximal domain is contained within 84 bases of the transcription initiation site and consists of three elements which appear to interact with the TATA factor(s) and CCAAT-box-binding transcription factor and SP1, respectively. The proximal domain is sufficient for near-maximal basal expression to rodent cell lines. The distal promoter domain consists of sequences upstream of -84 and is necessary in conjunction with the proximal domain for full basal expression in human cell lines. Although in BALB/c 3T3 cells the distal promoter domain plays little role in basal expression, it is functional as evidenced by the ability to compensate efficiently for mutations in the proximal CCAATC homology. The distal domain does not compensate as efficiently for proximal-domain mutations in HeLa cells. Basal expression of this human hsp70 promoter is, therefore, determined by multiple elements. Fewer elements are required for basal expression in rodent cell lines than in human cell lines, suggesting that there are significant differences between the rodent and human transcription apparatuses.